Opportunities, challenges and feasibilities of Zero-Power IoT in 5G advanced - Xu, Weijie; Zuo, Zhisong; He, Chuanfeng; Hu, Rongyi; Cui, Shengjiang; Shao, Shuai; Zhang, Zhi; Yang, Ning (IEEE/CIC International Conference on Communications in China - Workshops (Online), 2021)
In this paper, we firstly present some vertical use cases that have their specific services requirements which cannot be fulfilled with the existing IoT (Internet Of Things) technologies. Then a novel IoT system supporting zero-power terminals is proposed for 3GPP (3rd Generation Partnership Project) to cover these untouched vertical use cases. The IoT system uses back-scattering and RF (Radio Frequency) power harvesting thus the terminal has distinguished merits of ultra-low complexity, ultra-low cost, small size and battery-less. It can well match the requirements of the identified use cases. However, such a IOT system faces great challenges on the aspects such as services coverage, system efficiency, security management and access procedure etc. Finally, we give an overview of the possibilities to resolve these issues via developing a cellular IoT network and using 3GPP expertise.